Prove that the ratio of the sum of odd terms, Mathematics

If there are (2n+1)terms  in an AP ,prove that the ratio of the sum of odd terms and the sum of even terms is (n+1):n

Ans:    Let a, d be the I term & Cd of the AP.

∴ ak = a + (k - 1) d

s1 = sum to odd terms

s1 = a1 +  a3 + ......... a 2n + 1

s1  = n +1/2 [a1 + a2 n +1 ]

= n + 1/2 [2a1 + 2nd]

s1 = (n + 1) (a + nd)

s2 = sum to even terms

s2 = a2 + a4 + ..... a 2n

s2  = n/2 [a2 + a2n  ]

= n/2 [a + d + a + (2n - 1)d]

=n [a + nd]

∴ s1 : s2 = (n +1)(a nd )/n(a nd )

= n+1/n

Posted Date: 4/8/2013 6:05:06 AM | Location : United States







Related Discussions:- Prove that the ratio of the sum of odd terms, Assignment Help, Ask Question on Prove that the ratio of the sum of odd terms, Get Answer, Expert's Help, Prove that the ratio of the sum of odd terms Discussions

Write discussion on Prove that the ratio of the sum of odd terms
Your posts are moderated
Related Questions
Q. What are Mutually Exclusive events? Mutually Exclusive Events are mutually exclusive if they cannot occur at the same time. For example, if you roll one die, you canno

Slope-intercept form The ultimate special form of the equation of the line is possibly the one that most people are familiar with.  It is the slope-intercept form.  In this if

write an equation for a functionthat gives the value in ech table .


.what are 20 math integer equations that equal 36?..


For a population with a mean of μ=70 and a standard deviation of o=20, how much error, on average, would you expect between the sample mean (M) and the population mean for each of

what is the are of a square that is 2 inches long and 2 inches wide?

Proof of Sum/Difference of Two Functions : (f(x) + g(x))′  = f ′(x) +  g ′(x)  It is easy adequate to prove by using the definition of the derivative.  We will start wi

Prove that a m + n + a m - n  =2a m Ans:    a m + n = a 1 + (m + n - 1) d a m-n = a 1 + (m - n -1) d a m = a 1 + (m-1) d Add 1 & 2 a m+n + a m-n  =